Aspiring to become an engineer in Hong Kong: effects of engineering education and demographic background on secondary students' expectation to become an engineer. (2nd November 2018) - Kutnick, Peter; Chan, Rosanna Yuen-Yan; Chan, Cecilia Ka Yuk; Good, David; Lee, Betty Pok-Yee; Lai, Veronica Ka Wai
ABSTRACT: Many post-industrial societies have seen a decline in secondary school students' aspirations to become an engineer. Hong Kong (HK) is a post-industrial region within a larger industrialising society where no current study identifies engineering aspirations of secondary students. A representative sample of HK (3724 students/23 schools) explored engineering attitudes, perceptions, motivation, efficacy and curricular/extracurricular experiences using a purposely defined questionnaire. Contributions of these factors to students' aspirations were differentiated into individual and school contexts using hierarchical linear modelling and structural equation modelling. Descriptive analyses identified boys and younger students in single-sex schools had the most positive attitudes towards engineering but school-based engineering opportunities did not provide significant contributions to students' aspirations. Aspirations were affected by students' engineering efficacy, practical 'hands-on' experience and limited science, technology, engineering and mathematics (STEM) curricular experience. Similarities between HK and many post-industrial societies, and curriculum/pedagogical implications concerning efficacy for secondary school engineering education are identified.